Identification, Characterization, and Epidemiological Analysis of Lactococcus garvieae Fish Isolates Obtained in a Period of Eighteen Years - Ivo Sirakov; Tanya V. Strateva; Vasil Svetoslavov Boyanov; Petya Orozova; Daniel Yordanov; Nikolina Rusenova; Raina Gergova; Svetoslav G. Dimov; Bilyana Sirakova; Vladimir Radosavljević; Liliya Boyanova; Ivan Mitov (Microorganisms)
Lactococcosis caused by Lactococcus garvieae is a bacterial infection affecting fish with a considerable economic impact. Recently, L. garvieae has established itself as an opportunistic pathogen in humans. The aim of the current study was to test classical and molecular-biological methods for the identification of L. garvieae and examine antimicrobial susceptibility and capsule production, an important virulence factor. Additionally, tests for differentiation from closely related species, as well as epidemiological typing, were performed. In a period of 18 years (2002–2019), 24 isolates presumptively identified as L. garvieae were collected from Oncorhynchus mykiss and Salmo salar fish obtained either from retail stores or fish farms. In order to confirm the species, optimized PCR-based protocols were used. As a result, 21 of the tested strains were proved to be L. garvieae (n = 21). The remaining three isolates were Lactococcus lactis, Streptococcus iniae, and Enterococcus faecalis. Epidemiological typing by randomly amplified polymorphic DNA was performed. Except for a single KG+ isolate, all other strains belonged to the European capsular serotype KG−. All L. garvieae isolates showed susceptibility to all tested antibiotics with the exception of clindamycin, which was a diagnostic sign. A thorough optimization of diagnostic methods is essential to determining the etiology of specific infections affecting the personnel at risk in fish farms, the food industry, or within the broader community.